1998
DOI: 10.1093/glycob/8.5.509
|View full text |Cite
|
Sign up to set email alerts
|

Further characterization of the binding of human recombinant interleukin 2 to heparin and identification of putative binding sites

Abstract: We have previously provided compelling evidence that human recombinant interleukin 2 (IL-2) binds to the sulfated polysaccharides heparin, highly sulfated heparan sulfate and fucoidan. Here we show that IL-2 binding is dependent on heparin chain length, but with fragments as small as 15-mers retaining binding activity. The addition of exogenous heparin has no effect on the in vitro biological activity of IL-2. In addition soluble IL-2 receptor alpha and beta polypeptides do not compete with heparin for the bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 38 publications
1
33
0
1
Order By: Relevance
“…This antibody-(IL-2) fusion protein retained the binding specificity of the antibody and cytokine biological activity similar to that of rhIL-2 [69]. We have also observed that anti-HER2/neu IgG3-(IL-2) retains the heparin-binding activity of IL-2 [70], a property that allows the binding of this cytokine to glycosaminoglycans present in the surface of cells [71] and that may play a role in the control of T-cell responses by IL-2 [72]. The authors explored the in vivo efficacy of anti-HER2 /neu IgG3-(IL-2) as a direct antitumor agent in a murine colon carcinoma cell line expressing human HER2/neu (CT26-HER2/neu), which was injected subcutaneously into immunocompetent syngeneic BALB/c mice.…”
Section: Antibody-(il-2) Fusion Proteinsmentioning
confidence: 58%
“…This antibody-(IL-2) fusion protein retained the binding specificity of the antibody and cytokine biological activity similar to that of rhIL-2 [69]. We have also observed that anti-HER2/neu IgG3-(IL-2) retains the heparin-binding activity of IL-2 [70], a property that allows the binding of this cytokine to glycosaminoglycans present in the surface of cells [71] and that may play a role in the control of T-cell responses by IL-2 [72]. The authors explored the in vivo efficacy of anti-HER2 /neu IgG3-(IL-2) as a direct antitumor agent in a murine colon carcinoma cell line expressing human HER2/neu (CT26-HER2/neu), which was injected subcutaneously into immunocompetent syngeneic BALB/c mice.…”
Section: Antibody-(il-2) Fusion Proteinsmentioning
confidence: 58%
“…Sherblom et al (11) and Zanetta et al (12) reported that IL-2 recognizes high-mannose type glycans with five or six mannosyl residues as determined by the plate method. Later, Najjam et al (13) found that rhIL-2 binds to heparin specifically. However, since the addition of heparin did not show any inhibitory effect on IL-2-dependent cell proliferation, it was suggested that the interaction between IL-2 and heparin is not related to such activity.…”
Section: Interleukin-2 (Il-2)mentioning
confidence: 99%
“…However, our laboratory (9) and others (10,11) recently demonstrated that IL-2 binds to the extracellular matrix, suggesting the possibility that bound IL-2 might contribute to immune responsiveness. We tested this concept in model systems in which the functional effects of bound vs free IL-2 could be compared.…”
Section: Propagation and Control Of T Cell Responses By Heparanmentioning
confidence: 99%
“…Because IL-2 has been reported to bind collagen and mannose as well as heparan sulfate (9 -11, 20), we asked whether IL-2 must bind heparan sulfate in vivo to manifest this function. To address this question, we compared T cell responses generated in the presence of WT IL-2, with responses generated using a mutant IL-2 that does not bind heparan sulfate (11). The mutant IL-2, bearing a proline for threonine substitution at aa 51, has equivalent bioactivity to that of WT IL-2 in vitro (21,22).…”
Section: And Ref 9)mentioning
confidence: 99%